EFFECTS OF FEBUXOSTAT ON CAROTID INTIMA-MEDIA THICKNESS IN ASYMPTOMATIC HYPERURICEMIA: A RANDOMIZED CLINICAL TRIAL (PRIZE). (April 2021) - Tanaka, Atsushi; Taguchi, Isao; Teragawa, Hiroki; Ishizaka, Nobukazu; Murohara, Toyoaki; Node, Koichi
Abstract : Objective: Elevated levels of serum uric acid (SUA) increase the risk of gout and may be associated with the risk of cardiometabolic disorders and subsequent cardiovascular disease. Clinical evidence regarding the effects of xanthine oxidase (XO) inhibitors on atherosclerosis is lacking. The purpose of the study was to test whether treatment with febuxostat, a non-purine selective inhibitor of XO, delays carotid intima-media thickness (IMT) progression in patients with asymptomatic hyperuricemia. Design and method: This was an investigator-initiated, multicenter, randomized, controlled, open-label clinical trial undertaken at 48 Japanese sites. A total of 514 adults, who had both asymptomatic hyperuricemia with SUA >7.0 mg/dL and maximum IMT of the common carotid artery (CCA) 1.1 mm or greater at screening, were equally allocated to receive either dose-titrated febuxostat (10–60 mg daily) or non-pharmacological lifestyle modification for hyperuricemia as a control-arm. The primary endpoint was the percentage change from baseline in mean IMT of the CCA at 24 months. Key secondary outcomes included other carotid ultrasonographic parameters, SUA, and adverse events. Results: Compared with the control group, febuxostat had no significant effect on the primary endpoint (1.2% [95% CI, -0.6% to 3.0%] in the febuxostat group vs 1.4% [95% CI, -0.5% to 3.3%] in the control group; between-group difference [febuxostat-control], -0.2% [95% CI, -2.3% to 1.9%]; P = 0.83) and any other carotid ultrasonographic parameters. At 24 months, the between-group difference [febuxostat-control] in the SUA change from baseline was significant (-2.65 mg/dL [95% CI, -2.93 mg/dL to -2.37 mg/dL]; P < 0.001), and gout arthritis occurred only in the control group (4 patients [1.6%]). There were three deaths in the febuxostat group and seven in the control group during follow-up. Conclusions: In Japanese patients with asymptomatic hyperuricemia, 24 months of febuxostat treatment did not delay carotid atherosclerosis progression, compared with non-pharmacological care. These findings do not support the use of febuxostat for delaying carotid atherosclerosis in this population. However, febuxostat treatment was tolerable and did not increase the incidence of cardiovascular and all-cause mortality.